Structure elucidation of sweet-tasting cycloartane-type saponins from ginseng oolong tea and Abrus precatorius L. leaves. Issue 20 (18th October 2018) - Stavrianidi, Andrey; Stekolshchikova, Elena; Rodin, Igor; Godovikov, Ivan; Shpigun, Oleg
Abstract: The composition of ginseng oolong a widely used tea product was investigated. A new sweet-tasting cycloartane-type saponin 3β- O -[β-D-glucuronopyranosyl(1→2)]-β-D-6-acetylglucopyranosyl)-(20 S, 22 S )-3β, 22-dihydroxy-9, 19-cyclolanost-24-en-26, 29-oic acid (9 ), along with five new compounds, was identified in the methanolic extract of the ginseng oolong tea. Structural elucidation was conducted by spectroscopic methods, including 1D- and 2D-NMR, HR-MS, HPLC-LITMS/MS. It was shown that these compounds have different sugar chains connected to the abrusogenin molecule. Then saponin profiles of four commercially available ginseng oolong samples and Abrus precatorius L. leaves were compared and the presence of three known abrusosides and six new acetyl and malonyl abrusogenin derivatives was proved. The original ginsenosides were not detected in the extract, therefore, abrusosides could serve as a replacement responsible for the sweet taste of the tea. Abstract :